GENE-16. EVALUATING THE UTILITY OF INTEGRATED CLINICAL SEQUENCING FOR CHILDHOOD NEURO-ONCOLOGY PATIENTS: THE TEXAS KIDSCANSEQ STUDY - Mangum, Ross (Neuro Oncol, 2019)
Genomic sequencing technologies have facilitated the unbiased examination of cancer genomes, allowing rational prioritization of candidate genes and pathways for biological study and clinical application. Clinical experience with these methods as “precision oncology” strategies for children with central nervous system (CNS) tumors remains unproven. Over the past several years, a number of pilot studies of precision oncology have provided early clues regarding the feasibility, clinical utility, and limitations of genome-scale testing, emphasizing the critical importance of both tumor and germline results for patient care. These studies provide a foundation for incorporation of genomic testing into prospective clinical trials utilizing biomarker-driven treatment assignments in the care of pediatric cancer patients. To more rigorously compare the diagnostic utility of clinical genomic tests, the Texas KidsCanSeq study, an NHGRI and NCI-funded Clinical Sequencing Evidence Generating Research (CSER) Program project, was activated in June 2018. This study, which will enroll 1100 patients from six Texas institutions, aims to compare the diagnostic yield of targeted panel testing (comprehensive pediatric cancer-focused DNA and RNA panels utilized clinically at Texas Children’s Cancer Center) versus more extensive genomic testing (exome sequencing, transcriptome sequencing, copy number array) of formalin-fixed paraffin-embedded tumor and blood samples. Additionally, study oncologists are being surveyed regarding the downstream implications of these tests on decision-making related to the use of molecularly targeted therapies and/or enrollment on clinical trials. Early examples of CNS tumor cases with clinically-actionable mutations include two patients with midline high grade glioma (HGG) harboring activating PIK3CA mutations (15 year old male with thalamic HGG and PIK3CA p.Glu542Lys; 7 year old female with pontine HGG and PIK3CA p.Glu545Gly) that are potentially targetable by PI3K inhibitors or combined PI3K/MTOR inhibitors. These cases highlight the potential utility of molecular testing of pediatric CNS tumors for identification of novel therapies and relevant clinical trials.